Prevalence of Unexplained Left Ventricular Hypertrophy by Cardiac Magnetic Resonance Imaging in MESA. Issue 8 (16th April 2019) - Massera, Daniele; McClelland, Robyn L.; Ambale‐Venkatesh, Bharath; Gomes, Antoinette S.; Hundley, W. Gregory; Kawel‐Boehm, Nadine; Yoneyama, Kihei; Owens, David S.; Garcia, Mario J.; Sherrid, Mark V.; Kizer, Jorge R.; Lima, Joao A. C.; et al.
Abstract : Background: Hypertrophic cardiomyopathy is defined as unexplained left ventricular (LV) hypertrophy (wall thickness ≥15 mm) and is prevalent in 0.2% of adults (1:500) in population‐based studies using echocardiography. Cardiac magnetic resonance imaging (MRI) allows for more accurate wall thickness measurement across the entire ventricle than echocardiography. The prevalence of unexplained LV hypertrophy by cardiac MRI is unknown. MESA (Multi‐Ethnic Study of Atherosclerosis) recruited individuals without overt cardiovascular disease 45 to 84 years of age. Methods and Results: We studied 4972 individuals who underwent measurement of regional LV wall thickness by cardiac MRI as part of the MESA baseline exam. American Heart Association criteria were used to define LV segments. We excluded participants with hypertension, LV dilation (≥95% predicted end‐diastolic volume) or dysfunction (ejection fraction ≤50%), moderate‐to‐severe left‐sided valve lesions by cardiac MRI, severe aortic valve calcification by cardiac computed tomography (aortic valve Agatston calcium score >1200 in women or >2000 in men), obesity (body mass index >35 kg/m 2 ), diabetes mellitus, and current smoking. Sixty‐seven participants (aged 64±10 years, 9% female) had unexplained LV hypertrophy (wall thickness ≥15 mm in at least 2 adjacent LV segments), representing 1.4% (1 in 74) participants, 2.6% of men and 0.2% of women. Prevalence was similar across categories of race/ethnicity. Hypertrophy was focal in 17 (25.4%), intermediate in 44 (65.7%), and diffuse in 5 (7.5%) participants. Conclusions: The prevalence of unexplained LV hypertrophy in a population‐based cohort using cardiac MRI was 1.4%. This may have implications for the diagnosis of patients with hypertrophic cardiomyopathy and will require further study.